The Effect of Service Time, Facilities, Location, and Price Affordability on Patient Satisfaction at dr. Ranny Clinic - Megan Caroline Santoso Sie; Innocentius Bernarto (Budapest International Research and Critics University, 2022)
Patient satisfaction is defined as a patient assessment of the expectation and reality received by the patient at a health care facility. This study was conducted to determine the effects of service time, facility, location, and price affordability on patient satisfaction at dr. Ranny Clinic. This research used quantitative methods and the data collection technique by distributing questionnaires, using non probability sampling method with convenience sampling technique. The samples of this research were 220 respondents. The data were obtained and processed using partial least square- structural equation modeling (PLS- SEM) with the Smart-PLS software. The result of this study shows that the facility and price affordability has a positive effect on patient satisfaction. However, location and service time does not have a positive effect on patient satisfaction.